Candida utilis candidaemia in premature infants: a retrospective single-centre study - Sheng Zhang; Qiuping Li; Lu Zhuang; Zhichun Feng (BMJ Publishing Group, 2023)
This retrospective study was conducted in a neonatal intensive care unit in Beijing. Patients whose blood culture yielded Candida utilis during hospitalisation from January 2009 to December 2017 were enrolled. Thirteen preterm infants of median gestational age 29.85 weeks were included. Laboratory tests on the day of onset showed thrombocytopaenia in 11 patients, granulocytopaenia in eight and elevated C-reactive protein in seven. No fungal endophthalmitis, renal infection, carditis or involvement of other end organs was observed in any of the cases. All 13 patients were cured after fluconazole therapy.